Thermal Modeling and Analysis of Active and End Windings of Enclosed Permanent-Magnet Synchronous In-Wheel Motor Based on Multi-Block Method - Tang, Yue; Chen, Lei; Chai, Feng; Chen, Tanci (IEEE transactions on energy conversion, 2020)
This paper presents an accurate modeling method to investigate the thermal performance of the windings under steady state. The model considers the heat conduction of active windings and heat convection of end windings. To verify the validity of this model, a 20/24 poles/slots permanent magnet (PM) in-wheel motor is taken as an example. Firstly, the temperature distribution of the active windings in the slot is calculated by a multi-block 2-D temperature field model, which is verified by the model built according to the reality. The numerical results of blocks model agree well with those of the real model. Secondly, a 3-D temperature field model with the end windings is built on the 2-D blocks model. Furthermore, to include the air inside the motor, computational fluid dynamics (CFD) has been utilized, and the numerical results are experimentally verified. Finally, the distribution of the heat transfer coefficient (HTC) of the end windings and the influence of rotor speed on the HTC are investigated. These HTCs acquired from CFD results and empirical formulas are compared and analyzed carefully.